Peran Media Berbasis ICT (Information Communication Technologi) Terhadap Hasil Belajar Peserta Didik - M. Danish Sumantri; Aulia Ramadhani; Dhaifah Khairunnisa. B; Sani Safitri; Syarifuddin Syarifuddin (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The development of information and communication technology (ICT) has brought major changes to the world of education, especially in terms of the media used to support the teaching and learning process. The use of ICT-based media offers various advantages, such as fast access to information, more interesting learning materials, and a more flexible and personalized approach. This article aims to analyze the role of ICT-based media in improving student learning outcomes. In this discussion, it is explained how the use of ICT can enrich learning experiences, increase student motivation, and support more collaborative and independent learning. Even though there are various benefits, this article also identifies several challenges faced in implementing ICT-based media, such as gaps in technology access, limited infrastructure, and a lack of digital skills among teachers and students. Based on this analysis, this article concludes that although ICT-based media has great potential to improve learning outcomes, the success of its implementation is very dependent on infrastructure readiness, training for teachers, and awareness of the importance of technology integration in the education curriculum. For this reason, there needs to be a more planned strategy and support from all parties to maximize the use of ICT in education